2012
DOI: 10.1242/jeb.068528
|View full text |Cite
|
Sign up to set email alerts
|

A test of alternate models for increased tissue nitrogen isotope ratios during fasting in hibernating arctic ground squirrels

Abstract: SUMMARYWe describe two models explaining the increase in tissue nitrogen isotope ratios ( Supplementary material available online at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 58 publications
(78 reference statements)
5
52
0
Order By: Relevance
“…However, higher δ 15 N values in the baleen of EC-WG whales occurred in the most recently grown baleen in summer, when they are known to feed heavily on zooplankton blooms. Recent studies such as Aguilar et al (2014) and Matthews and Ferguson (2015) observed a similar pattern of 15 N enrichment in summer in baleen plates of a larger sample of EC-WG bowhead whales and in fin whales (Balaenoptera physalus), respectively, that are also contrary to the proposal that fasting leads to higher δ 15 N values (e.g., Best and Schell 1996;Cherel et al 2005;Lee et al 2012). It is more likely that summer feeding in regions with different baseline values or different types of prey led to depletion in 15 N (e.g., Aguilar et al 2014).…”
Section: Seasonal Cycling: Bcb and Ec-wg Individual Whalesmentioning
confidence: 71%
“…However, higher δ 15 N values in the baleen of EC-WG whales occurred in the most recently grown baleen in summer, when they are known to feed heavily on zooplankton blooms. Recent studies such as Aguilar et al (2014) and Matthews and Ferguson (2015) observed a similar pattern of 15 N enrichment in summer in baleen plates of a larger sample of EC-WG bowhead whales and in fin whales (Balaenoptera physalus), respectively, that are also contrary to the proposal that fasting leads to higher δ 15 N values (e.g., Best and Schell 1996;Cherel et al 2005;Lee et al 2012). It is more likely that summer feeding in regions with different baseline values or different types of prey led to depletion in 15 N (e.g., Aguilar et al 2014).…”
Section: Seasonal Cycling: Bcb and Ec-wg Individual Whalesmentioning
confidence: 71%
“…Urea and Ca 2+ are of particular interest due to the unique changes in the animal's regulation of the urea cycle and Ca 2+ signaling, which occur during mammalian hibernation (Chilian and Tollefson 1976;Wang et al , 2002Stenvinkel et al 2013;Lee et al 2012;Epperson et al 2011). The addition of 5 and 100 mM of urea seemed to have no effect on the binding of NFATc1, c3, or c4 to DNA, with Fig.…”
Section: Effect Of Camentioning
confidence: 99%
“…There have been few attempts to explore the effects of metabolic mechanisms within a single species despite the obvious advantage that this has on controlling metabolic variability. In this study, we explore the effect of nutritional stress on Δ (Deschner et al 2012;Lee et al 2012;Hobson and Quirk 2014;BenDavid et al 2012), there is still a need for further experiments on a greater number of species and with varying dietary restrictions.…”
Section: Introductionmentioning
confidence: 99%